Corporate social responsibility as a way to sustainable employment - Muszyńska, Karolina (Społeczna odpowiedzialność biznesu jako droga do zrównoważonego zatrudnienia, 2020)
The purpose of this article is to identify the relationship between the declared activities in line with corporate social responsibility and the implementation of diversity management concepts. The paper presents the essence of corporate social responsibility as an element of company strategy, and the importance of the concept of managing diversity of employees in building an organizational culture based on mutual respect and a sense of security of employees, and thus increasing the efficiency and innovation of the company, by recognizing the individual characteristics of the people employed. An in-depth interview method was used, conducted on the basis of a non-standardized interview questionnaire with HR directors of domestic companies. The obtained empirical material was presented as a case study
Econometrics = Ekonometria, 2020, Vol. 24, No. 3, s. 59-69
Keywords: corporate social responsibility; diversity; business strategy; sustainable development; społeczna odpowiedzialność biznesu; zarządzanie różnorodnością; kapitał ludzki; strategia biznesowa; zrównoważony rozwój